Analisis Yuridis Penentuan Kriteria Daluwarsa Dalam Putusan Mahkamah Konstitusi Nomor 118/PUU-XX/2022 - Belana, Loudy; Romaida Hutabarat, Rugun (Universitas Ekasakti, 2023)
There are several factors that influence the removal of the right to prosecute, one of which is due to expiration. The complainant or victim believes that the act of abolishing prosecution, especially due to expiration, means releasing the suspect from criminal responsibility, the abolition of prosecution, especially due to expiration, may not provide justice for them. This writing uses normative or doctrinal legal research because it uses information sources of norms with prescriptive research specifications. This research method includes document review or literature review, and the writing approach used is the statutory approach and the case approach. Public perception and trust in the current legal system can be harmed by the elimination of expired prosecutions. As in the Constitutional Court Decision Number 118/PUU-XX/2022, this is because the Criminal Code, especially Article 79 Paragraph (1), does not provide legal certainty to victims of criminal acts if the calculation begins after the counterfeit goods are used.